The School of God Pedagogy and Rhetoric in Calvin s Interpretation of Deuteronomy - Blacketer, Raymond A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This study examines Jean Calvin s attempt to nurture a godly society and further his vision of ecclesiastical and societal reform by means of sound pedagogy and persuasive rhetoric. The focus of this work is Calvin s interpretation of the latter Pentateuch, and particularly the book of Deuteronomy. The author examines Calvin s exegesis and rhetoric in his commentary on the latter Pentateuch, as well as the sermons that Calvin preached on Deuteronomy material that has received little scholarly attention. Calvin s interpretations are compared with the preceding exegetical tradition and with his contemporaries, and always considered in the contexts of the early modern interest in classical rhetoric and that of the reform of church, theology, and society in Switzerland and beyond. Commonly held assumptions about Calvin s methodology, such as his alleged aversion to rhetoric and the scholarly fixation on his laconic style, are challenged, nuanced, and corrected. Because of its fresh, contextual approach to Calvin s thought, this study will be an important resource for students of the history of exegesis as well as for Calvin scholars, and it will appeal to seminary as well as university students.
Acknowledgements. Abbreviations. Introduction: Calvin s Old Testament Exegesis in Context -- 1: L École de Dieu. Pedagogy from the Pulpit. Preaching and Pedagogy in Calvin s Vision of a Godly Society -- 2: Ample Preaching. The Rhetoric of Calvin s Sermons -- 3: Calvin s Sermons on Deuteronomy. A Course in Remedial Education -- 4: Calvin s Pedagogically Correct Commentary On Moses Perfect History. Improving on Perfection -- 5: Calvin on the Fourth Commandment. The Rhetoric of Rest -- 6: Calvin on Deuteronomy 10:1-2. Smooth Stones, Teachable Hearts -- 7: Calvin on Deuteronomy 21:18-21. The Case of the Incorrigible Son. Conclusion. Bibliography. Index.
Keywords: Religion; History; Religious Studies; Religious Studies, general; History, general; Electronic books